Deciphering signaling mechanisms and developmental dynamics in extraembryonic mesoderm specification from hESCs - Baohua Niu; Da Wang; Yingjie Hu; Yundi Wang; Gaohui Shi; Zhongying Chen; Lifeng Xiang; Chi Zhang; Xuesong Wei; Ruize Kong; Hongzhi Cai; Weizhi Ji; et al. (Nature Communications)
Abstract Extraembryonic mesoderm (ExM) is crucial for human development, yet its specification is poorly understood. Human embryonic stem cell (hESC)-based models, including embryoids and differentiated derivatives, are emerging as promising tools for studying ExM development. Despite this, the signaling mechanisms and developmental dynamics that underlie ExM specification from hESCs remain challenging to study. Here, we report that the modulation of BMP, WNT, and Nodal signaling pathways can rapidly (4-5 days) and efficiently ( ~90%) induce the differentiation of both naive and primed hESCs into ExM-like cells (ExMs). We reveal that ExM specification from hESCs predominantly proceeds through intermediates exhibiting a primitive streak (PS)-like gene expression pattern and delineate the regulatory roles of WNT and Nodal signaling in this process. Furthermore, we find that the initial pluripotent state governs hESC-based ExM specification by influencing signal response, cellular composition, developmental progression, and transcriptional characteristics of the resulting ExMs. Our study provides promising models for dissecting human ExM development and sheds light on the signaling principles, developmental dynamics, and influences of pluripotency states underlying ExM specification from hESCs.